Streptozotocin-induced diabetes duration is important to determine changes in the number and basophily of myenteric neurons - LUZMARINA HERNANDES; ROBERTO BARBOSA BAZOTTE; PATRÍCIA GAMA; MARCÍLIO HUBNER DE MIRANDA-NETO (Arquivos de Neuro-Psiquiatria)
The aim of present study was to evaluate the number and basophily of cell bodies of myenteric neurons in the ileum of rats with diabetes mellitus induced by streptozotocin. Four groups of rats were used: diabetes was induced in two (D) whereas the other two worked as controls (N). Animals were sacrificed six (6N, 6D) or nineteen (19N, 19D) weeks after diabetes induction. A segment of the terminal portion of the ileum of each rat was obtained and stained with Giemsa's solution, for whole-mount preparation studies. Forty fields were analyzed in each animal, and the number and basophily intensity of cell bodies were recorded. After counting, the following mean numbers of neurons/mm² were obtained: 6N=593.1 ± 95.75, 6D=639.1 ± 130.8, 19N=580.1 ± 175.6 and 19D=402.0 ± 144.8. The analysis of basophily shown that highest frequency of neurons with weak/intermediary basophily was verified in 6D group (55.3%), whereas the groups 6N, 19N e 19D presented 38%, 36% e 40% respectively. The statistical analysis showed that a long period is necessary to decrease the number of neurons/mm² in the rat ileum after diabetes induction, and that there was a reduction in basophily intensity in diabetic rats after 6 weeks of treatment, and such cells do not recover after a longer period (19 weeks).